Análise comparativa entre os métodos ACN/PCN e ACR/PCR para classificação de resistência de pavimentos flexíveis aeroportuários - Castro, Cecília Catarina Oliveira de (2021)
The ACN/PCN (Aircraft Classification Number/Pavement Classification Number) method of structural classification of airport pavements, in force since 1983, will be replaced by the ACR/PCR (Aircraft Classification Rating/Pavement Classification Rating) by 2024, which will adopt an mechnanistic-empirical procedure based on elastic linear layer analysis, , which can result in a better assessment of the structural capacity of the pavements. The replacement of methods can generate many questions for the technical and scientific community about the differences in the input data, the form of data analysis, the results, the advantages and limitations still remaining, and hinder the adherence to the ACR/PCR method and and its application in a rational way. The lack of a reliable method that reports the structural capacity of pavements is detrimental to the analysis of pavement life and performance. This work presents a comparative analysis between the ACN/PCN and ACR/PCR methods, in order to verify the change of methods and the impacts on the service life, on the admissibility of takeoff and landing operations, and on the management of pavements. For this, two flexible coating landing and take-off runways located in Brazil were evaluated with the help of COMFAA and FAARFIELD software. The results show that flexible pavements governed by the ACN/PCN method provide structures with reduced durability, in which the subgrade and the surface layer more quickly reach their failure criteria. On the other hand, when governed by the ACR/PCR Method, the subgrade has a useful life close to that of the project and the coating has a durability of more than 10 years. Furthermore, the results suggest that overload acceptance criteria for the ACR/PCR method should be revised and adjusted according to the configuration of the landing gears of the aircraft models that make up the traffic mix. The replacement of the method will be positive for the Airport Pavement Management System, from a structural point of view, but, in some cases, it may change the admissibility of operation of aircraft that are currently permitted. Finally, it is noteworthy that the ACR/PCR method also has limitations, mainly in considering the behavior of materials as being linear-elastic, isotropic and homogeneous and allowing aerodrome operators to estimate the modulus of elasticity from data of CBR, and should be used with caution.